Supply Chain Network Design: A Case Study In a Dairy Company - Lucas Cedroni Fava; Mauro Sampaio (International Journal of Supply Chain Management, 2020)
This research seeks the development of a supply chain network design, aiming to determine the optimal location of a dairy distribution center and its ideal inventory capacity, considering the location of a company’s facilities as a key factor for financial success, since costs such as inventory and transportation are influenced by network projects. Variables such as logistical costs, taxes, inventories, etc., are considered during the execution of the network design. This study contributes to the area of network design in the supply chain, having a quantitative and exploratory nature. A single case study was carried out in the dairy company, analyzing documents and financial information to decide on the most advantageous place for the distribution center. The Supply Chain Guru software for network optimization, developed by Llamasoft, was used to support this project. This tool has been previously studied and analyzed for this use, since it can bring relevant and complex outcomes. The result was that the optimal location for the new distribution center would be at one of the company’s existing plants, which would bring an economy close to R$ 100,000 in one year of operation.